The economic crisis in Greece short account of events and actors - Boubouka, Angeliki (My University, 2019)
This chapter provides a concise overview of the events related to the economic crisis in Greece, during the period 2009-2018, and of the political and other actors involved with the crisis management. The chapter briefly discusses the dimensions of the crisis, as well as the repercussions of the crisis and of the policies implemented to tackle it at the economic, social, and political levels. This short overview will help to embed the research in its socio-political context.
Keywords: Sovereign Debt Crises; Austerity Policy; New Public Management